Fly ash based geopolymer concrete: A review - Nath, Pradip; Sarker, Prabir (Research Publishing Services, 2013)
Geopolymer binder is an emerging alternative of ordinary Portland cement (OPC) for concrete because of its comparable physical and mechanical properties shown in the recent studies. The current published literature indicates the prospect of geopolymer concrete for structural use. However, the overall performance and functionality under various environmental conditions has not yet been well documented. This paper reviews the works conducted on the fly ash based geopolymer concrete (FGPC) and summarizes its performance as a concrete material. The properties of FGPC are influenced by many factors such as the types and composition of fly ash (aluminosilicate source), final composition of chemical ingredients (alkaline activators), water to solid ratio and curing condition (temperature and relative humidity). Most of the previous studies were based on heat-cured or steam-cured samples. The implications of the current studies were analyzed to identify the critical factors holding back the wide application of FGPC. Further research areas for the improvement of FGPC were identified.